HUBUNGAN ANEMIA, KEK DAN USIA IBU HAMIL DENGAN KEJADIAN BBLR DI PUSKESMAS JATIROTO KABUPATEN LUMAJANG TAHUN 2022 - Munifah, Chotijatul; Rohmatin, Homsiatur; Farianingsih, Farianingsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Low Birth Weight (LBW) is newborn have weigh less than 2500 gram. There are some reason birth LBW among other age mother, gestation interval, paritas, Anemia, CED, gestational age, pregnancy history, and gestational complication. The general objective of this study was to identify and analyze the correlation between Anemia, KEK and Age pregnant women with evens LBW at the Jatiroto Health Center, Lumajang Regency. The population in this study were all pregnant women who gave birth at the Jartiroto Health Center, Lumajang Regency, totaling 592 people. Sampling in this study used the Slovin formula, in order to obtain a total sample of 239 people. In this study used the Chi-square test with contingency coefficient, using SPSS. Based on the results of the analysis, it shows that there is a relationship between Anemia, KEK and Age pregnant women with event LBW births at the Jatiroto Health Center, Lumajang Regency, indicated age by a significance value of 0.000, less than 0.05. It shows that less material age 20 year and age over 35 year can improve LBW birth. Anemia pregnancy, CED pregnancy also cause LBW birth. with CED can increase LBW births. So there must be effort guard pregnancy so pregnant mother not giving birth Low Birth Weight.